New Public Management: Literatur Riview Gaya Baru Pemerintah dalam Mengelola Layanan Publik - Kusmawati, Siska Dila; Anggraini, Katherina Estherika; Wicandra, Ajeng Ayu; Dewi, Antika; Ardini, Lilis (Politeknik Raflesia Press, 2025)
In the era of globalization and digitalization, public demand for fast, transparent, and accountable public services is continually increasing. New Public Management (NPM) has emerged as a new paradigm in bureaucratic reform by adopting private sector management principles to enhance efficiency, accountability, and innovation in public service delivery. This study employs a qualitative descriptive approach through a literature review to examine the concept, implementation, as well as the strengths and weaknesses of NPM in the governmental context. The literature review indicates that the implementation of NPM has significantly contributed to improving performance and transparency in public services, particularly through the utilization of digital technology and objective performance measurement systems. However, NPM also faces challenges such as internal resistance, limited resources, and difficulties in reconciling private management principles with the social values and equity inherent in the public sector. The study suggests the need for strategic adaptation based on local contexts and an enhancement in human resource capacity to optimize bureaucratic reform. It is expected that the findings of this research will provide strategic recommendations for policymakers to realize a more modern, responsive, and quality-oriented public administration.